Bidirectional sex‐dependent regulation of α6 and β3 nicotinic acetylcholine receptors by protein kinase Cε. (10th August 2020) - Moen, Janna K.; DeBaker, Margot C.; Myjak, Julia E.; Wickman, Kevin; Lee, Anna M.
Abstract: Nicotine and alcohol are the most commonly abused substances worldwide and are frequently coabused. Nicotinic acetylcholine receptors (nAChRs) containing the α6 and β3 subunits are expressed in neural reward circuits and are critical for nicotine and alcohol reward. nAChRs are dynamically regulated by signaling molecules such as protein kinase C epsilon (PKCε), which impact transcription of α6 and β3 subunit mRNA ( Chrna6 and Chrnb3, respectively). Previous work found decreased expression of Chrna6 and Chrnb3 transcripts in the ventral midbrain of male PKCε −/− mice, who also consume less nicotine and alcohol compared with wild‐type (WT) littermates. Using RT‐qPCR, we show that female PKCε −/− mice have higher expression of Chrna6 and Chrnb3 transcripts in the ventral midbrain, which functionally impacts nAChR‐dependent behavior as female but not male PKCε −/− mice exhibit locomotor hypersensitivity to low‐dose (0.25 mg/kg i.p.) nicotine. Female PKCε −/− mice show no differences in alcohol‐induced sedation in the loss‐of‐righting reflex assay (4.0 g/kg i.p.) compared with WT littermates, whereas male PKCε −/− mice have enhanced sedation compared with WT mice. Female PKCε −/− mice also show reduced immobility time in response to varenicline (1.0 mg/kg i.p.) compared with WT littermates in the tail suspension test, and this effect was absent in male mice. Additionally, we found that female PKCε −/− mice show altered alcohol and nicotine consumption patterns in chronic voluntary two‐bottle choice assays. Our data reveal a bidirectional effect of sex in the transcriptional regulation of nicotinic receptors by PKCε, highlighting the importance of studying both sexes in preclinical animal models. Abstract : We describe a bidirectional effect of sex in the transcriptional regulation of nicotinic acetylcholine receptors (nAChRs) by PKCε, which correlates with distinct consequences on nAChR‐dependent behavior.